Islamic fintech, financial inclusion, and MSME sustainability: Evidence from a mixed-method study in Indonesia’s digital economy - Widagdo, Ridwan; Rokhlinasari, Sri; Wartoyo, Wartoyo (Universitas Islam Indonesia, 2026)
IntroductionMicro, Small, and Medium Enterprises play a critical role in economic development, employment generation, and inclusive growth, particularly in developing countries. Despite their importance, many MSMEs face persistent barriers in accessing formal financial services, which limits their ability to sustain and scale their businesses. The emergence of Islamic financial technology offers an alternative pathway by providing digital, sharia-compliant financial services that can enhance financial inclusion and support sustainable business practices.ObjectivesThis study aims to analyze the role of Islamic fintech in improving financial inclusion and its impact on MSME sustainability. It also examines the mediating role of financial inclusion in the relationship between Islamic fintech and sustainable MSME performance within a digital business environment.MethodThe study employs a mixed-method approach using a sequential exploratory design. Qualitative data were collected through in-depth interviews with MSME stakeholders in Region III Cirebon, Indonesia, while quantitative data were obtained from 96 MSMEs using structured questionnaires. The analysis combines qualitative thematic interpretation with quantitative modeling using Structural Equation Modeling with Partial Least Squares to test the proposed relationships among variables.ResultsThe findings indicate that Islamic fintech has a positive and significant effect on financial inclusion, while financial inclusion significantly enhances MSME sustainability. The results also confirm that financial inclusion mediates the relationship between Islamic fintech and MSME sustainability, suggesting that the impact of Islamic fintech operates indirectly through improved access to financial services. Qualitative findings further reveal that sustainable MSME models emphasize digital transformation, institutional support, and integration of economic and social practices.ImplicationsThe study highlights the importance of strengthening Islamic fintech ecosystems to improve financial access and support MSME sustainability. It also underscores the need for policies that promote financial literacy, digital readiness, and regulatory support to maximize the benefits of fintech adoption.Originality/NoveltyThis research contributes to the literature by providing empirical evidence on the mediating role of financial inclusion in the relationship between Islamic fintech and MSME sustainability. It offers a comprehensive perspective by integrating qualitative and quantitative approaches within the context of a developing economy.